Long-Term Results From Tonsillectomy in Adults - Senska, Götz (Dtsch Arztebl Int, 2015)
BACKGROUND: Tonsillectomy is performed more than 400 000 times in the European Union each year, making it one of the most common operations. Nonetheless, there have been only a few long-term studies of quality of life after tonsillectomy. METHODS: In 2004, data on the quality of life after tonsillectomy were obtained from adult German-speaking tonsillectomy patients by means of the Glasgow Benefit Inventory and a questionnaire specifically designed for that study. The present study concerns the further follow-up of these patients, sometimes many years later. 114 patients with recurrent tonsillitis were included in this descriptive study. RESULTS: Of the 114 patients, 97 (85%) provided further data at 14 months, and 71 (62%) at ca. 7 years. The Glasgow Benefit Inventory revealed postoperative improvement of quality of life at 14 months and at 7 years, with median values of 16.67 points (quartile 11.11/25) and 13.89 points (quartile 8.33/25) (p = 0.168). The mean number of annual episodes of sore throat fell from 10 preoperatively to 2 postoperatively (p = 0.0001). The number of visits to the doctor, the intake of analgesic drugs and antibiotics, and the number of medical absences from work also declined significantly over the period of observation. CONCLUSION: Tonsillectomy was associated with a long-lasting improvement of health and quality of life, and with lower utilization of medical resources. The 62% response rate at 7 years leaves the question open whether patients with a favorable postoperative course may have been more likely than others to participate in the study.